Development and Realization of Approach for Defining Quality Objectives of Carmaker According to Results of Cars Warranty Period - V. N. Kozlovskiy; D. V. Aydarov; S. A. Shanin (Наука и техника)
Approaches based on such quality management principles as “consumer orientation” and “decision making on the basis of factual data” are of particular importance for the development of Russian automotive industry under current conditions. In order to solve key problems concerning quality and product competitiveness it is necessary to take efficient and substantiated management decisions which are based on a detailed analysis of the results in respect of cars warranty period. Such technology contributes to improvement of quality management processes, creation of opportunities for enhancement of customer satisfaction and sustainable development of carmakers. The paper is updating a problem of development and realization of a new approach to define quality objectives for automotive corporations. Historical analysis has been made in respectof changes in cars quality indicators for one of the leading Russian automakers. The paper presents conventional methodology which is used at enterprises to define quality objectives for new cars being under warranty period. A new approach for determination of target indicators for product quality in automotive industry has been proposed on basis of the analysis of the best practice in organizing process to monitor quality of cars in operation. The approach takes into account a number of indicators of key importance in the formation of product competitiveness of automotive corporations. A common platform has been implemented for development and monitoring of quality objectives for cars in operation. The developed platform meets current and prospwctive tendencies. Application of the platform and its elements in the carmakers practice provides opportunities for harmonious improvement of the quality management system and it is aimed at improvement of product competitiveness.